Precise quantification of mixtures of bispecific IgG produced in single host cells by liquid chromatography-Orbitrap high-resolution mass spectrometry. Issue 8 (16th November 2016) - Yin, Yiyuan; Han, Guanghui; Zhou, Jianhui; Dillon, Michael; McCarty, Luke; Gavino, Lou; Ellerman, Diego; Spiess, Christoph; Sandoval, Wendy; Carter, Paul J.
ABSTRACT: Bispecific IgG are heterotetramers comprising 2 pairs of heavy and light chains. Co-expression of the 4 component chains in a single host cell typically yields the desired bispecific IgG plus up to 9 additional incorrect chain pairings. Several protein engineering strategies have been reported to facilitate the heterodimerization of antibody heavy chains or cognate pairing of antibody heavy and light chains. These technologies have been used to direct the efficient assembly of bispecific IgG in single host cells and minimize unwanted chain pairings. When purifying bispecific IgGs, the identification and quantification of low levels of closely related IgG contaminants are substantial analytical challenges. Here we have developed a robust high-throughput method for quantitative analysis of bispecific IgG preparations using novel online liquid chromatography in conjunction with an extended mass range Orbitrap-based high-resolution mass spectrometer. A mathematical method was developed to estimate the yields of the 2 isobaric species, namely the desired bispecific IgG and the light chain-scrambled IgG. The analytical methods described herein are anticipated to be broadly applicable to the development of bispecific IgG as drugs and potentially to other complex next-generation biotherapeutics.